2017
DOI: 10.1111/rda.13084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oestrous synchrony between embryo donors and recipients, embryo quality and state on the pregnancy rate in beef cattle

Abstract: This study aimed to evaluate the effect of oestrous synchrony between donors and recipients and the embryo quality on the pregnancy rate in beef cow recipients. The experiment was performed over two years at an embryo transfer (ET) centre in Southern Brazil. Ninety Aberdeen Angus cows were subjected to superovulation (SOV) protocols, resulting in the recovery of 1,048 transferable embryos. Eleven groups were formed with intervals of 6 hr, from -30 to +30 hr, with respect to recipient versus donor oestrous dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
1
14
0
2
Order By: Relevance
“…Only Code I and II quality embryos are considered as transferable (Bó & Mapletoft, ). Previous studies have reported that the quality of embryos affects pregnancy rates in embryo transfer programmes in cattle (Bényei et al, ; Hasler et al, ; Rodrigues et al, ). Ferraz et al () found that pregnancy rates following the transfer of Code I and II quality embryos were 42.2% and 32.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only Code I and II quality embryos are considered as transferable (Bó & Mapletoft, ). Previous studies have reported that the quality of embryos affects pregnancy rates in embryo transfer programmes in cattle (Bényei et al, ; Hasler et al, ; Rodrigues et al, ). Ferraz et al () found that pregnancy rates following the transfer of Code I and II quality embryos were 42.2% and 32.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Ferraz et al () found that pregnancy rates following the transfer of Code I and II quality embryos were 42.2% and 32.8%, respectively. Bényei et al () and Rodrigues et al () reported that the rate of pregnancy following the transfer of Code I quality embryos was higher than Code II. As a result of this study, it was found that pregnancy rate decreases as embryo quality decreases.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the synchrony in the timing of oestrus and post-ovulatory uterine changes between the donor and recipient is crucial, as they are likely to be determinants of pregnancy rates following embryo transfer. Pregnancy rates were 64% when cattle recipients expressed oestrus within six hours of the donor cow, with pregnancy rates dropping to 56% and 48% when recipients were in oestrus within 12 or 24 h, respectively, of the donor cow [44]. Not only does this demonstrate that there is an optimal environment for an embryo to survive (discussed in detail herein) it also demonstrates the importance of the synchrony of the recipient animals used in an assisted reproductive technology.…”
Section: Assisted Reproductive Technologiesmentioning
confidence: 88%
“…Òàê, íàïðèìåð, â èññëåäîâàíèè Rodrigues M.C.C. ñ ñîàâòîðàìè [23], â õîäå êîòîðîãî áûëè ïîëó÷åíû îò êîðîâ-äîíîðîâ àááåðäèí-àíãóññêîé ïîðîäû 1048 ýìáðèîíîâ, ïåðåñàaeåííûõ ðåöèïèåíòàì, ïîêàçàíî, ÷òî àñèíõðîííîñòü ïîëîâîãî öèêëà ìåaeäó äîíîðîì è ðåöèïèåíòîì ñ ðàçíèöåé â ±30 ÷àñîâ ñíèaeàåò óðîâåíü ïðèaeèâëÿåìîñòè òðàíñïëàíòèðóåìîãî ýìáðèîíà ñ 50% äî 36%. Äðóãèìè àâòîðàìè áûëî îòìå÷åíî, ÷òî àñèíõðîííîñòü ïîëîâîãî öèêëà ìåaeäó äîíîðîì è ðåöèïèåíòîì ñ ðàçíèöåé â 24 ÷àñà íå ñíèaeàåò ïîêàçàòåëè ïðèaeèâëÿåìîñòè [20].…”
Section: äëÿ öèòèðîâàíèÿ / For Citationunclassified
“…Ñîãëàñíî èìåþùèìñÿ íà ñåãîäíÿøíèé äåíü äàííûì, â îòå÷åñòâåííîé è çàðóáåaeíîé ïðàêòèêå ïðèìåíåíèÿ äàííîé òåõíîëîãèè ïðè ïåðåñ÷åòå íà îáùåå êîëè÷åñòâî èñïîëüçîâàííûõ êîðîâ-ðåöèïèåíòîâ ïîêàçàòåëü ïðèaeèâëÿåìîñòè òðàíñïëàíòèðîâàííûõ ýìáðèîíîâ âàðüèðóåò â äèàïàçîíå 40-60%, ÷òî îäíîâðåìåííî óêàçûâàåò, â ñðåäíåì, íà 50 % ñëó÷àåâ íåóäà÷íûõ ïåðåñàäîê, ïðèâîäÿùèõ ê ýêîíîìè÷åñêèì ïîòåðÿì ïðè ðàçâåäåíèè êðóïíîãî ðîãàòîãî ñêîòà [9][10][11]. Âìåñòå ñ òåì, ïðè íàëè÷èè ýòîé ïðîáëåìû, ñâèäåòåëüñòâóþùåé î âåðîÿòíîì äîñòèaeåíèè ïîðîãà ðåçóëüòàòèâíîñòè òåõíîëîãèè òðàíñïëàíòàöèè ýìáðèîíîâ êðóïíîãî ðîãàòîãî ñêîòà, äàííàÿ òåõíîëîãèÿ íà ñåãîäíÿøíèé äåíü ÿâëÿåòñÿ îäíèì èç ãëàâíûõ èíñòðóìåíòîâ, ñòèìóëèðóþùèõ ðàçâèòèå îòðàñëè aeèâîòíîâîäñòâà âî ìíîãèõ ñòðàíàõ ìèðà.…”
unclassified